Pakistan's army from an institutional pressure group to final arbiter in governance - Kukreja, Veena (2015)
This article seeks to focus on the role of the military in governance of Pakistan-from institutional interest groups to final arbiter of the country-and how this situation has developed. The case of Pakistan represents an apt example of how an apolitical military could slowly be drawn into the political field due to the failure of political institutions, politicians, political parties, low political mobilisation, and international factors. In the first instance, being a well organised and skilled organisation, it helped every government to maintain law and order, slowly became an important factor in the decision making process, and ultimately displaced the civil authority and became an arbiter. Besides, it also takes into account military's changing role and parameters in Pakistan. In the 1950s and 1960s under Ayub Khan the army played the role of an agent of modernisation. In the 1970s, it moved to conquer the people of East Pakistan and Baluchistan as a Punjabi-dominated army of a ruthless state. In the 1980s, it assumed its role as a defender of the dominant political ideology. Finally, the military has been able to translate its dominance over the state structure to become deeply entrenched in the political economy of the state. Thus, the military in Pakistan is the most formidable and autonomous political actor, capable of influencing the nature and direction of political change. - Reproduced.
Keywords: Interest groups - Pakistan; Pakistan. Army; Armed forces